Information System in The Analysis of The Spread of ALSINTAN in Kalawat District, Minahasa Utara Regency - Molenaar, Robert; Yaba, Akwila; Pakasi , Sandra Engelin (Jurnal Agroekoteknologi Terapan, 2025)
This research aims to develop a geographic information system to support the use of agricultural tools and machines in Kalawat District, North Minahasa Regency. This research was carried out for 2 months, starting in January-February 2022, with two stages, namely data collection at the research location in Kalawat sub-district, North Minahasa district, and data processing are made and displayed in tables and information maps. Equipment used Laptop Acer Aspire 5 A515, GPS Garmin and GPS Essential, Digital Camera, Smartphone Poco F3 Software (Software), Operating System Windows 10, ArcGIS 10.8, Microsoft Office Word 2013, Microsoft office excel 2013, Google Earth Pro 7.3.2 (64-bit), Postgre Structured Query Language (PostgreSQL) 10, PostGeographic Information System (PostGIS) and Mozilla Firefox. Research Results The making of an information system map for identifying the spread of ALSINTAN in Kalawat sub-district, North Minahasa district, has been carried out and is running well. Geographic Information System (ArcMap) can provide information related to agricultural tools and machinery in Kalawat District, North Minahasa Regency. This information system is very helpful and makes it easy for anyone who needs data and information about the availability of agricultural tools and machinery in Kalawat District, presented in the form of an interactive information map. In addition, the Information System (ArcMa) is useful for policymakers as a supporting tool in making decisions regarding the distribution and implementation of agricultural tools and machinery to farmers in the study location. Keywords: Information system, spread of agricultural machinery